2009
DOI: 10.1109/tevc.2008.2009460
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Memetic Framework

Abstract: Memetic algorithms (MAs) represent one of the recent growing areas in evolutionary algorithm (EA) research. The term MAs is now widely used as a synergy of evolutionary or any population-based approach with separate individual learning or local improvement procedures for problem search. Quite often, MAs are also referred to in the literature as Baldwinian EAs, Lamarckian EAs, cultural algorithms, or genetic local searches. In the last decade, MAs have been demonstrated to converge to high-quality solutions mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
102
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(103 citation statements)
references
References 47 publications
(40 reference statements)
0
102
0
1
Order By: Relevance
“…Example 2. Let the two parent individuals are (6,19,91,38,64) and (3,29,17,61,6), randomly generate the mask (1, 0, 0, 1, 0), then the two offspring after crossover are (6, 29, …”
Section: Representation and Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 2. Let the two parent individuals are (6,19,91,38,64) and (3,29,17,61,6), randomly generate the mask (1, 0, 0, 1, 0), then the two offspring after crossover are (6, 29, …”
Section: Representation and Operatorsmentioning
confidence: 99%
“…Recently, MAs have been well used across a wide range of problem domains. A lot of studies have demonstrated that MAs converge to high-quality solutions more efficiently than their conventional counterparts in many realworld applications [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. MAs have also been applied in the image processing field [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the analytical optimal solution is difficult to obtain even for relatively simple application problems. Researchers instead study the numerical optimization algorithm arises from almost every field, such as engineering design, systems operation, decision making, and computer science for example [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In [4] the classification of coordination methods has been extended and updated. The following four categories have been identified: 1) Adaptive Hyper-heuristic, where heuristic rules are employed (e.g., [8], [9], [10], [11]); 2) MetaLamarckian learning defined in [12], where the activation of the memes depends on their success, see also [13], [14], [15]; 3) Self-Adaptive and Co-Evolutionary, where the rules coordinating the memes are evolving in parallel with the candidate solutions of the optimization problem or encoded within the solution, see [16], [17], [18], [19]; and 4) Fitness DiversityAdaptive, where the activation of the memes depends on a measure of the diversity (e.g., [20], [21], [6], [22], [23]). As a general idea, the algorithmic designer attempts to have a system which performs the coordination automatically.…”
Section: Introductionmentioning
confidence: 99%